Physician predictions of length of stay of patients admitted with heart failure. Issue 9 (17th May 2016) - Durstenfeld, Matthew S.; Saybolt, Matthew D.; Praestgaard, Amy; Kimmel, Stephen E.
Abstract : Physicians' ability to predict length of stay is understudied, particularly for patients with heart failure (HF) admissions. The objective of this prospective, observational cohort study was to measure the accuracy of inpatient physicians' predictions of length of stay at the time of admission of patients admitted to an academic tertiary care hospital with HF and to determine whether level of experience improves accuracy. The patients included 165 adults consecutively admitted with heart failure, about whom 415 predictions were made within 24 hours of admission. Mean and median lengths of stay were 10.9 and 8 days, respectively. The mean difference between predicted and actual length of stay was statistically significant for all groups: interns, −5.9 days (95% confidence interval [CI]: −8.2 to −3.6, P < 0.0001); residents, −4.3 days (95% CI: −6.0 to −2.7, P = 0.0001); attending cardiologists, −3.5 days (95% CI: −5.1 to −2.0, P < 0.0001). There were no differences in accuracy by level of experience ( P = 0.61). Physicians, regardless of experience, underestimate length of stay of patients admitted with HF. Journal of Hospital Medicine 2016;11:642–645. © 2016 Society of Hospital Medicine